Perempuan, Jilbab, dan Solidaritas Kemanusiaan: Studi Gerakan Perempuan Berhijab Pasca Tragedi New Zealand - Wildani Hefni (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2019)
The movement of humanities solidarity that is widely voiced is the women's movement specifically to wear the hijab (hijab) as a form of solidarity with Muslims. women take a role that is based on the awareness of the importance of togetherness wearing headscarves as a symbol of strength to reject any rhetoric of hatred on any basis, be it identity, religion, race, and ethnicity. This paper describes the veiled women's movement as a form of humanitarian solidarity in the aftermath of the New Zealand tragedy. A descriptive qualitative study of library research was conducted using the Durkheiminism approach. This study produces findings that the hijab has a symbol of religious meaning that is closely related to solidarity and social identity. The veil becomes a symbol of social solidarity as well as resistance to abuse. The hijab movement was born as a collective act to revive the spirit of togetherness among religious followers in combating various acts of radicalism and terrorism.